Pengaruh Model Self-Regulated Learning Berbantuan Media Educaplay Terhadap Scientific Thinking Skill dan Disiplin Diri Siswa Sekolah Dasar - Musonah Musonah; Wanda Nugroho Yanuarto (LPPM Institut Pendidikan Nusantara Global, 2026)
This study analyzed the effect of Self-Regulated Learning (SRL) supported by Educaplay on elementary school students' scientific thinking skills and self-discipline, and examined the relationship between the two variables. The study employed a quantitative approach with a quasi-experimental nonequivalent control group design. The population consisted of fourth-grade elementary students in the Dwijo Utomo cluster, Kemranjen District, Banyumas Regency. The sample involved two schools: an experimental class (n=17) and a control class (n=15). Data were collected through a scientific thinking skills test, self-discipline observation sheets, and documentation, and analyzed using normality and homogeneity tests, independent sample t-test, simple linear regression, and Pearson correlation. The findings showed that the experimental class obtained a higher posttest mean score in scientific thinking skills (88.88) than the control class (71.67), with a significant difference (p=0.000). The experimental class also showed a higher mean score in self-discipline (89.59) than the control class (74.47), with a significant difference (p=0.000). Regression analysis indicated that SRL supported by Educaplay had a positive and significant effect on scientific thinking skills (B=3.810; β=0.663; p=0.000) and self-discipline (B=3.065; β=0.681; p=0.000). In addition, a significant positive relationship was found between scientific thinking skills and self-discipline in the experimental class (r=0.665; p=0.004). These findings confirm that integrating SRL with Educaplay is effective in simultaneously developing elementary students' cognitive and affective outcomes.